Volatility Spillover between Stock Market and Foreign Exchange Market in Indonesia - Wiryono, Sudarso Kaderi; Widjonarko, Yohanes Edward (SBM ITB, 2009)
Foreign exchange rate risk is one the market risk factors that effects investments. Understanding the foreign exchange risk exposure of each sector is necessary to set foreign exchange risk management. This paper examines the volatility spillover effect between the stock market and foreign exchange rate market. The significant volatility spillover existence is an evident that the volatility in one market affects the volatility in the other market. This research used EGARCH volatility spillover model developed by Malhotra, Niranjan, and Swain (2007) in Indiaâ€™s study case. The model is applied to examine the volatility spillover of foreign exchange market toward each sector indices in Indonesia. The findings of the research are that USD/IDR fluctuation gives the most significant exposure to Indonesian stock marketâ€™s of JSX indices as well as on the majority sectors, followed by JPY/IDR fluctuation and EUR/IDR fluctuation, while GBP/IDR does not give a significant volatility spillover toward the sector. Most sectors also have a different exposure one another so different focus of foreign exchange risk management is needed.Keywords:Â foreign exchange risk, volatility spillover, risk management